The Multi-Faced Extracellular Vesicles in the Plasma of Chronic Kidney Disease Patients - Georgatzakou, Hara T.; Pavlou, Efthimia G.; Papageorgiou, Effie G.; Papassideri, Issidora S.; Kriebardis, Anastasios G.; Antonelou, Marianna H. (Frontiers in Cell and Developmental Biology, 2020)
Extracellular vesicles (EVs) are membrane-enclosed nanoparticles released by most cells in body fluids and extracellular matrix. They function as signal transducers in intercellular communication, contributing to the maintenance of cell and tissue integrity. EVs biogenesis is deregulated in various pathologies, in structural and functional connection to the pathophysiology of donor cells. Consequently, EVs are considered diagnostic and monitoring factors in many diseases. Despite consensus as to their activity in promoting coagulation and inflammation, there is evidence suggesting protective roles for EVs in stress states. Chronic kidney disease (CKD) patients are at high risk of developing cardiovascular defects. The pathophysiology, co-morbidities and treatment of CKD may individually and in synergy affect extracellular vesiculation in the kidney, endothelium and blood cells. Oxidative and mechanical stresses, chronic inflammation and deregulation of calcium and phosphate homeostasis, are established stressors of EV release. EVs may affect the clinical severity of CKD by transferring biological response modifiers between renal, vascular, blood and inflammatory cells. In this Review, we focus on EVs circulating in the plasma of CKD patients. We highlight some recent advances in understanding of their biogenesis, the effects of dialysis and pharmacological treatments on them and their potential impact on thrombosis and vascular defects. The strong interest of the scientific community to this exciting field of research may reveal hidden pieces in the pathophysiology of CKD and thus, innovative ways to treat it. Overcoming gaps in EV biology and technical difficulties related to their size and heterogeneity will define the success of the project.